Effects of Buprenorphine on the Memory and Learning Deficit Induced by Methamphetamine Administration in Male Rats - Etaee, Farshid; Rezvani-Kamran, Arezoo; Komaki, Somayeh; Asadbegi, Masoumeh; Faraji, Nafiseh; Raoufi, Safoura; Taheri, Mohammad; Kourosh-Arami, Masoumeh; Komaki, Alireza (Frontiers in Behavioral Neuroscience, 2021)
Little is known about the effects of methamphetamine (Meth) and buprenorphine (Bup) on memory and learning in rats. The aim of this investigation was to examine the impact of Meth and Bup on memory and learning. Fourteen male Wistar rats weighing 250 to 300 g were assigned to four groups: Sham, Meth, Bup, and Meth+Bup and were treated for one week. Spatial learning and memory, avoidance learning, and locomotion were assessed using the Morris water maze, passive avoidance learning, and open field tests, respectively. Meth and Bup impaired spatial learning and memory in rats. Co-administration of Meth+Bup did not increase the time spent in the target quadrant compared to Meth alone in the MWM. The Bup and Meh+Bup groups were found with an increase in step-through latency (STLr) and a decrease in the time spent in the dark compartment (TDC). Meth and Bup had no effects on locomotor activity in the open field test. Bup showed a beneficial effect on aversive memory. Since Bup demonstrates fewer side effects than other opioid drugs, it may be preferable for the treatment of avoidance memory deficits in patients with Meth addiction.